STUDI KOMPARATIF BAHASA OGAN DESA TANGSI LONTAR DAN DESA BANJAR SARI KABUPATEN OKU - Samsul Anam; Darningwati Darningwati (Puitika, 2018)
The objectives of this study were firstly to discrabe the dialect similarities and differences of Oganese language of Tangsi Lontar village in pengandonan district and Banjar Sari in Semidang Aji district in case of phonology and lexicology. Secondly, this intralingual matching study also described  the factors beyond those similarities and differences. The result af the study showed that there more differences than similarities between Oganese language of Tangsi Lontar and Banjar Sari. There were 106 (53%) different and 94 (47%) similart words out of 200 words analyzed by researchers. From those 106 different words, 52 words were different in terms of lexicon and 54 words were different in terms of phoneme. The differences of phoneme occured in 48 changes of vowel sound, 3 word were different in consonant, and 3 words were different in vowel and consonant phonemes. In addition, geographical area, interaction, and society environment were the factors beyond those similarities and differences. In sum, Oganese language of Tangsi Lontar and Banjar Sari was the same but they had different dialect. Keywords: study, comparative, Ogan language